Case report: Novel ETFDH compound heterozygous mutations identified in a patient with late-onset glutaric aciduria type II - Zhu, Sijia; Ding, Dongxue; Jiang, Jianhua; Liu, Meirong; Yu, Liqiang; Fang, Qi (Frontiers in Neurology, 2023)
Glutaric aciduria type II (GA II) is an autosomal recessive metabolic disorder of fatty acid, amino acid choline metabolism. The late-onset form of this disorder is caused by the defect in the mitochondrial electron transfer flavoprotein dehydrogenase or the electron transfer flavoprotein dehydrogenase (ETFDH) gene. So far, the variable clinical course of late-onset GA II has brought a great challenge for its diagnosis. In this study, we reported a 21-year-old Chinese man with muscle weakness, vomiting and severe pain. Muscle biopsy revealed myopathological patterns of lipid storage myopathy, and urine organic acid analyses showed slightly increase of glycolic acid 2. All above results were consistent with GA II. Whole Exome Sequencing (WES) followed by bioinformatic and structural analysis revealed two compound heterozygous missense mutations: c.1034A > G (p.H345R) on exon 9 and c.1448C>A (p.P483Q) on exon 11, which were classified as “likely pathogenic” according to American College of Medical Genetics and Genomics (ACMG). In conclusion, this study described the phenotype and genotype of a late-onset GA II patient. The two novel mutations in ETFDH were found in this case, which further expands the list of mutations found in patients with GA II. Because of the treatability of this disease, GA II should be considered in all patients with muscular symptoms and acute metabolism decompensation such as hypoglycemia, acidosis.